Adaptability evaluation of pavement structure to replacement treatment subgrade of black cotton soil. Issue 1 (30th June 2020) - Luan, Yingcheng; Ma, Yuan; Zhang, Weiguang; Zhang, Yuqing; Ma, Tao; Lee, Jusang
Abstract: Aiming at the typical engineering problem of black cotton soil (BCS) subgrade under the alternation of dry and wet climate in the region of Nairobi, Kenya, this paper takes the pavement structure as the research object, and the numerical calculation model of BCS subgrade is established based on the consolidation coupling theory of unsaturated soil. Taking the modulus and thickness of the subbase as variables, the deformation characteristics and additional stresses of different pavement structures are analysed. Then the adaptability of different pavement structures to replacement treatment subgrade of BCS is evaluated by gray incidence decision analysis method. The results show that whatever the pavement structure is, neither subgrade modulus nor thickness is sensitive to the pavement surface deformation, and the deformation differences between each pavement structure are more obvious in wet season; the additional stress at control layer bottom and pavement surface decreases with the increase of subbase modulus, whereas the stress may increase at subbase bottom; the additional stress at subbase bottom, control layer bottom and pavement surface all decreases with the increase of subbase thickness for pavement Structure I and II. For pavement Structure III, the change of subbase thickness is not sensitive to the additional stress at the control layer bottom and pavement surface, whereas the stress at subbase bottom increases with the increase of subbase thickness. It is concluded that the most adaptable structure is pavement Structure I, which can minimize the comprehensive level of pavement settlement and additional stress.